17.46% efficient and highly stable carbon-based planar perovskite solar cells employing Ni-doped rutile TiO2 as electron transport layer. (August 2018) - Liu, Xingyue; Liu, Zhiyong; Sun, Bo; Tan, Xianhua; Ye, Haibo; Tu, Yuxue; Shi, Tielin; Tang, Zirong; Liao, Guanglan
Abstract: Organometal trihalide perovskite solar cells (PSCs) with carbon counter electrode (CE) have attracted tremendous interest due to their remarkable properties such as low cost and high stability. However, carbon-based PSCs always suffer from much lower power conversion efficiency (PCE) than the counterparts with noble metal cathode. Herein, we demonstrate a carbon-based planar heterojunction PSC using high-crystallinity Ni-doped rutile TiO2 as electron transport layer (ETL) for the first time, while copper phthalocyanine (CuPc) is introduced as hole transport layer (HTL). It is found that Ni doping can shift the Fermi level of the ETL upward and increase the charge mobility of the TiO2 film, thus enhancing the charge transport and extraction. An optimized PCE of 17.46% was obtained after 0.01 M Ni doping, comparable to or even better than devices with state-of-the-art doped Spiro-OMeTAD as HTL and Au as CE. To the best of our knowledge, this is the highest efficiency that has been reported for carbon-based PSCs. By contrast, the pristine TiO2 -based device only displayed a PCE of 15.82%. Detailed superior capability of Ni-doped TiO2 in facilitating charge transfer and suppressing carrier recombination are revealed by Hall effect and photoluminescence (PL) as well as electrochemical impedance spectroscopy (EIS) measurements. Furthermore, the use of highly stable CuPc and commercial carbon makes as-prepared PSCs exhibit excellent stability with no obvious decline in PCE after being stored in ambient air for 1200 h. This work presents an important step forwards to the commercialization of carbon-based PSCs with high efficiency and long-term stability. Graphical abstract: 17.46% efficient and highly stable carbon-based planar perovskite solar cells employing Ni-doped rutile TiO2 as electron transport layer are demonstrated. Ni-doping boosts the power conversion efficiency of the PSCs from 15.82% to 17.46% due to the improved conductivity and charge mobility as well as the suppressed recombination. fx1 Highlights: The highest efficiency among carbon-based perovskite solar cell is achieved. A novel and facile approach to prepared Ni-doped rutile TiO2 was proposed. Ni doping improved the conductivity and charge mobility of pristine TiO2 . Cost-effective and highly stable CuPc and Carbon were introduced as HTL and electrode. Low manufacturing costs and excellent stability were obtained for our devices.